2020
DOI: 10.1073/pnas.2000849117
|View full text |Cite
|
Sign up to set email alerts
|

Analogy between periodic patterns in thin smectic liquid crystal films and the intermediate state of superconductors

Abstract: Spontaneous breaking of symmetry in liquid crystal (LC) films often reveals itself as a microscopic pattern of molecular alignment. In a smectic-A LC, the emergence of positional order at the transition from the nematic phase leads to periodic textures that can be used as optical microarrays, templates for soft lithography, and ordering matrices for the organization and manipulation of functional nanoparticles. While both 1d and 2d patterns have been obtained as a function of the LC film thickness and applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 60 publications
1
21
0
1
Order By: Relevance
“…5b). In practice this texture forms in a very narrow interval of temperature above T N A , which depends on the sample thickness [23]. In a 25 µm-thick sample of 8CB this interval of temperature is of the order of 0.02 • C. Needless to say that our optical method to determine κ 31 can no longer be applied in this interval of temperature, which is a limitation of this method.…”
Section: Resultsmentioning
confidence: 99%
“…5b). In practice this texture forms in a very narrow interval of temperature above T N A , which depends on the sample thickness [23]. In a 25 µm-thick sample of 8CB this interval of temperature is of the order of 0.02 • C. Needless to say that our optical method to determine κ 31 can no longer be applied in this interval of temperature, which is a limitation of this method.…”
Section: Resultsmentioning
confidence: 99%
“…Such methods could be of great benefit to structure prediction where the defects cannot be observed optically, for example, in thin films [39][40][41][42][43]. Furthermore, scenarios where partial smectic order exists, such as during the transition from the nematic to the smectic phase, may exhibit very complicated pretransitional structures [37,38,44,45], and few studies have addressed the connection between pattern formation and the peculiar critical behavior of liquid crystals at the nematicsmectic transition [46]. Dynamical phenomena-such as time-varying layer spacing [47], interactions between embedded particles [31], and the evolution of smectic films and bubbles [48][49][50]-also present difficult problems that appear to require numerical modeling.…”
mentioning
confidence: 99%
“…It was found that the director field geometry of nematics would strongly affect the geometry of subsequent smectic topological defects during the phase transition, which is rationalized by illustrating the similarity of ordering between nematics and smectics. Zappone et al 103 examined the smectic pattern conversion from one-dimensional (1D) streaks to 2D fan-shaped FCD arrays when cooling from nematics to smectics, Fig. 5b .…”
Section: Typical Thermotropic Liquid Crystal Architecturesmentioning
confidence: 99%